(untitled) (Economics and region, 2016)
Creating ordered the company cost structure requires the implementation of economically justified their classification on certain grounds, which should provide a comprehensive study and group information in the right context. Each sign describes the costs of certain side, so the more distinguished characteristics classification, the higher degree of knowledge objects. Common approach to the scientific classification of costs exists. This is a great range of costs that arise in the course of the company and its ambiguous nature. The division of costs for individual groups is rather arbitrary. Certain expenses included in different directions. As a result of generalization of existing approaches to the classification of expenditure proposed to group them according to the following criteria: organizational management, accounting and analytical, financial and economic. Enterprises considerably differ in process, organizational structure, relationships with partners and contractors, as well as the interdependence between different structural units inside. Characteristic features of the company, first of all, are in production, which is managed by the technology of production. Therefore, the content, amount, type and form of information needed to manage the production process, each company sets their own. This is particularly important proper organization and timeliness of cost accounting by product and units, proper organization of analytical accounting. Accordingly, the accounting and analytical criterion for classification of costs unites the following areas: the method of carrying value of the products, the composition, the ratio of the manufacturing processes types in relation to the reporting period, in relation to the finished product, inappropriately (for items costing), by type of goods (works, services) in order of computing, for inclusion in the estimate (costing). The financial and economic criterion for classification of the expenditures in terms of calculations, appropriateness and inclusion in the expenditure estimates. It covers the following areas: by type of costs in relation to the forms of labor, in relation to the form of value, the consumption of resources, feasibility of spending, in relation to existing rules, for the purpose of analysis, the term calculation. The present approach to the classification of expenditure as a whole covers all areas of activity and most accurately summarizes the types of costs that are unique industrial complex enterprises.